Relativistic Quantum Brayton Engine Based on Two Non-Interacting Dirac Particles in a One-Dimensional Potential Well - Nabila, Titis Qorin; Sukamto, Heru; Purwanto, Agus (Jurnal Fisika dan Aplikasinya, 2025)
A quantum heat engine converts heat into work based on the principles of quantum thermodynamics.This study investigates a quantum heat engine composed of two Dirac particles confined in a one-dimensional potential well. The potential well is limited to three discrete energy levels, and the two non-interacting Dirac particles are treated as identical. The system operates under a quantum Brayton cycle, consisting of isobaric and adiabatic processes. The total work output is calculated using the energy levels derived from the relativistic Dirac equation. The efficiency curve is obtained by plotting a theoretical expression as a function of the ratio $L_A/\lambda$, where $\lambda$ is the Compton wavelength. The efficiency increases monotonically with $L_A/\lambda$, approaching an asymptotic maximum, and is further enhanced by larger values of the parameter $\alpha$, which drive the engine toward near-optimal performance.